A brief overview of several earthquake catalog visualization methods - Pei He; Huai Zhang; Yaolin Shi (地球与行星物理论评)
Earthquake catalogs are crucial data for seismic hazard analysis and serve as essential information for studying lithospheric dynamics. They play a significant role in national economic development, earthquake analysis and forecasting, engineering seismic resistance, and earthquake disaster reduction. In geoscience, seismologists often utilize two-dimensional and three-dimensional scatter plots, magnitude-time (M-T) diagrams, and other visualization methods to explore relationships such as earthquake magnitude and frequency variations with epicenter locations, as well as the evolution of earthquake magnitude over time. With the continuous enhancement of seismic monitoring capabilities, the completeness of earthquake catalogs has been improving annually. However, traditional visualization methods are becoming increasingly inadequate for simultaneously representing associations among multiple variables. Moreover, for large-scale earthquake catalog data, issues like limited resolution leading to overlapping graphical elements can arise. This not only hampers the effective extraction of hidden knowledge from large-scale earthquake catalog data but may also convey misleading visual information. To address these challenges, this study proposes four distinct visualization methods for earthquake catalog data. These methods simultaneously encode information on earthquake magnitude and frequency variations with epicenter locations, occurrence times, and other variables, employing high-dimensional and multi-visual channel fusion techniques for comprehensive visualization. They efficiently represent the interrelationships among magnitude, frequency, occurrence time, and epicenter location in large-scale earthquake catalog data, providing a new reference for earthquake catalog visualization. Applying this approach, the study compares and validates these methods against traditional visualization techniques such as scatter plots and M-T diagrams using over 70000 earthquake catalog entries from the China Seismic Experimental Site between 2009 and 2021. The results effectively resolve the aforementioned issues and offer valuable insights into the visualization of large-scale earthquake catalog data. This contributes to a comprehensive understanding of the spatiotemporal distribution patterns of earthquake events, elucidates the underlying physical processes of earthquakes, and supports experts in researching, forecasting earthquakes, and improving seismic engineering design. The findings indicate that the Sichuan-Yunnan region exhibits high seismic activity and hazard levels, primarily concentrated near fault zones such as the Longmenshan Fault Zone. Areas like Tengchong also demonstrate elevated seismic activity, warranting attention to these regions characterized by high frequency but moderate magnitude earthquakes.